2009
DOI: 10.1007/s11258-009-9575-6
|View full text |Cite
|
Sign up to set email alerts
|

Mound building termites contribute to savanna vegetation heterogeneity

Abstract: With biomass densities comparable to large ungulates and megaherbivores, termites play a key functional role in many tropical savanna ecosystems. This study focuses on vegetated termite mounds (termitaria) constructed by the Termitidae species Macrotermes herus. We studied how resource rich termitaria affect graminoid herbs (Poaceae and Cyperaceae), forbs and woody species composition and diversity. The density of termitaria explained 89% of the variation in dense thickets in the area. Fire tolerant Acacia spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
165
6
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(187 citation statements)
references
References 48 publications
13
165
6
1
Order By: Relevance
“…While many ecologists may quibble about these exact labels, our goal was to understand these species' roles in controlling a key ecosystem process, biological nitrogen (N) fixation. In particular, although the importance of termites in biogeochemical cycling and, in some cases, the creation of heterogeneous habitat, is well recognized (e.g., Arshad 1981, Jouquet et al 2005, Moe et al 2009; see review in Jones 1990), the range of mechanisms by which they exert their effects have remained unclear, as has the spatial extent and patterning of their influences.…”
Section: Introductionmentioning
confidence: 99%
“…While many ecologists may quibble about these exact labels, our goal was to understand these species' roles in controlling a key ecosystem process, biological nitrogen (N) fixation. In particular, although the importance of termites in biogeochemical cycling and, in some cases, the creation of heterogeneous habitat, is well recognized (e.g., Arshad 1981, Jouquet et al 2005, Moe et al 2009; see review in Jones 1990), the range of mechanisms by which they exert their effects have remained unclear, as has the spatial extent and patterning of their influences.…”
Section: Introductionmentioning
confidence: 99%
“…Trees growing on-mound were regarded as woody vegetation lifeforms with diameter at the base (10 cm above the mound) greater than 6 cm as determined [28]. These were counted by two observers and actual population obtained following [29] sampling approach by two observers.…”
Section: Sampling and Datamentioning
confidence: 99%
“…Shrubs growing on and off-mound plots were woody plants below 3 m in height (determined by inclinometer) and have diameter less than 6 cm at 10 cm above the ground as determined by sliding Vernier caliper [28]. (transect).…”
Section: Sampling and Datamentioning
confidence: 99%
“…Termite-induced resource heterogeneity, such as soil composition (Sileshi et al 2010, Erpenbach et al 2013) and soil moisture , Konate et al 1999, induces this vegetation pattern. Spatial heterogeneity is also a factor, in that termite mounds act as refugia for plants from fire (Moe et al 2009, Joseph et al 2013) and flooding , Bloesch 2008. Okullo et al (2012a) suggested that large herbivores maintain termite-induced differences in savanna vegetation.…”
Section: Introductionmentioning
confidence: 99%